2020
DOI: 10.22541/au.158938596.67608241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parosmia is associated with relevant olfactory recovery after olfactory training

Abstract: Objectives This study aims to determine the association between parosmia and clinically relevant recovery in olfactory function in patients with smell loss receiving olfactory training. Design and setting This was a retrospective cohort study of patients that received olfactory training. Adult patients with the major complaint of quantitative smell loss were recruited and treated at several ENT clinics in German between 2008 and 2018. Participants A total of 243 participants were included. Main outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Fifth Sense, the UK charity for people affected by smell and taste disorders, was founded in 2012 and working together with patients our previous work has been able to demonstrate the very significant impact of olfactory disorders on those affected. 12 , 13 Whilst recent findings show that qualitative disorders may have a positive prognostic significance for the recovery of olfactory disorders 14 they do however present a particular source of distress to those affected whilst present. Previous studies of patients presenting with olfactory dysfunction have shown that parosmia was present in 34% and phantosmia present in 12% of patients presenting to a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth Sense, the UK charity for people affected by smell and taste disorders, was founded in 2012 and working together with patients our previous work has been able to demonstrate the very significant impact of olfactory disorders on those affected. 12 , 13 Whilst recent findings show that qualitative disorders may have a positive prognostic significance for the recovery of olfactory disorders 14 they do however present a particular source of distress to those affected whilst present. Previous studies of patients presenting with olfactory dysfunction have shown that parosmia was present in 34% and phantosmia present in 12% of patients presenting to a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…1543,1544,1617 A retrospective cohort study of 153 patients with PIOD undergoing OT therapy found that the presence of phantosmia failed to be associated with clinically relevant improvement in OF, but this only points away from phantosmia being a positive predictive factor and does not elucidate whether OT may be helpful for phantosmia itself in some patients. 1618 No clinical trials have been performed on this subject.…”
Section: G Phantosmia/parosmia Treatment 1 Medical Treatment Optionsmentioning
confidence: 99%